The Liver Retransplantation Risk Score: a prognostic model for survival after adult liver retransplantation. (16th July 2021) - Brüggenwirth, Isabel M. A.; Werner, Maureen J. M.; Adam, René; Polak, Wojciech G.; Karam, Vincent; Heneghan, Michael A.; Mehrabi, Arianeb; Klempnauer, Jürgen L.; Paul, Andreas; Mirza, Darius F.; Pratschke, Johann; Salizzoni, Mauro; et al.
Summary: High‐risk combinations of recipient and graft characteristics are poorly defined for liver retransplantation (reLT) in the current era. We aimed to develop a risk model for survival after reLT using data from the European Liver Transplantation Registry, followed by internal and external validation. From 2006 to 2016, 85 067 liver transplants were recorded, including 5581 reLTs (6.6%). The final model included seven predictors of graft survival: recipient age, model for end‐stage liver disease score, indication for reLT, recipient hospitalization, time between primary liver transplantation and reLT,  donor age, and cold ischemia time. By assigning points to each variable in proportion to their hazard ratio, a simplified risk score was created ranging 0–10. Low‐risk (0–3), medium‐risk (4–5), and high‐risk (6–10) groups were identified with significantly different 5‐year survival rates ranging 56.9% (95% CI 52.8–60.7%), 46.3% (95% CI 41.1–51.4%), and 32.1% (95% CI 23.5–41.0%), respectively ( P  < 0.001). External validation showed that the expected survival rates were closely aligned with the observed mortality probabilities. The Retransplantation Risk Score identifies high‐risk combinations of recipient‐ and graft‐related factors prognostic for long‐term graft survival after reLT. This tool may serve as a guidance for clinical decision‐making on liver acceptance for reLT. Abstract : The retransplantation risk score.